PENGARUH KEBIASAAN BELAJAR DAN LINGKUNGAN BELAJAR TERHADAP HASIL BELAJAR MATA PELAJARAN EKONOMI SMA NEGERI 1 KAYAN HULU - Susimardola Susimardola; Emilia Dewiwati Pelipa; Munawar Thoharudin (Jurnal Pendidikan Ekonomi (JURKAMI), 2022)
The success of a student's learning is not absolute only in the form of grades, but will be in the form of change, reasoning, discipline, skills and so on that lead to positive change. In this study, the factors related to the learning outcomes studied were study habits and student learning environment. The purpose of this study is to describe the influence of study habits and learning environment on learning outcomes of class X economics at SMA Negeri 1 Kayan Hulu. The research approach used is quantitative research with the form of research is correlation research. The population in the study was 104 students of SMA Negeri 1 Kayan Hulu with a sample of 82 students. The sampling technique was simple random sampling. The data collection technique used is a questionnaire. Analysis of the data used in this study is multiple linear regression. Based on the research that has been done, it shows that there is a partial and simultaneous influence of study habits and learning environment on the learning outcomes of class X economics at SMA Negeri 1 Kayan Hulu